AS CONTRIBUIÇÕ DO ASSISTENTE SOCIAL NO CAMPO DA PROMOÇÃO DA SAÚDE: DESAFIOS E POSSIBILIDADES. - Dias Quintino, Thiago; Tadeu Relo de Mattos, Augustus; Cristina Modesto Barbosa, Debora; Cassanho Forster, Aldaísa (Revista de Atencao Primaria a Saude)
This article focuses on studying the contribution of the social worker in health promotion. Based on the parameters for social worker actions in the health area, we seek to identify how their practice takes place, proposing actions that could strengthen the guarantee of social rights for people who use the health services, providing greater autonomy and social advancement to users of the Unified Health System (SUS). From a resizing on the activities of social service professionals, particularly in the field of health promotion, a challenge is raised to consider how social workers can effectively contribute to health promotion in municipalities, drawing on one of their competencies, that is, developing the coordination role within an intersectoral and interdisciplinary network.